PERSEPSI MAHASISWA NERS TERHADAP PELAKSANAAN PRECEPTORSHIP - Fathaniah, Farahiyah; Suci, Wice Purwani; Dewi, Yulia Irvani (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2025)
Preceptorship is a clinical learning method that plays a crucial role in guiding nursing students. The role of the preceptor is essential in helping students develop nursing skills, attitudes, and knowledge. Students' perceptions of preceptorship implementation can serve as an indicator of the success of clinical guidance. This study aims to describe the perceptions of professional nursing students regarding the implementation of preceptorship at the Faculty of Nursing, University of Riau. This research employed a descriptive quantitative design with a total sampling technique. A total of 171 students participated as respondents. Data were collected using the Nursing Clinical Teacher Effectiveness Inventory (NCTEI) questionnaire, which evaluates eight dimensions of preceptor competence. The results showed that 152 respondents (88.9%) had a positive perception of preceptorship implementation. The highest-rated dimensions included leadership (97.7%), clinical competence (97.1%), and professional and ethical behavior (97.1%). In conclusion, most students had a good perception of their preceptors, and preceptorship was considered to optimally support the clinical learning process. Keywords: perception, students, preceptorship, professional nurse Abstrak Preceptorship merupakan metode pembelajaran klinik yang berperan penting dalam membimbing mahasiswa keperawatan. Peran preceptor sangat menentukan dalam membantu mahasiswa mengembangkan keterampilan, sikap, dan pengetahuan keperawatan. Persepsi mahasiswa terhadap pelaksanaan preceptorship dapat menjadi indikator keberhasilan bimbingan klinik. Penelitian ini bertujuan untuk mengetahui gambaran persepsi mahasiswa terhadap pelaksanaan preceptorship pada mahasiswa profesi Ners di Fakultas Keperawatan Universitas Riau. Penelitian ini menggunakan desain deskriptif kuantitatif dengan teknik total sampling. Sebanyak 171 mahasiswa menjadi responden. Data dikumpulkan menggunakan kuesioner Nursing Clinical Teacher Effectiveness Inventory (NCTEI) yang menilai delapan dimensi kompetensi preceptor. Hasil menunjukkan bahwa 152 responden (88,9%) memiliki persepsi baik terhadap pelaksanaan preceptorship. Dimensi dengan penilaian tertinggi meliputi kepemimpinan (97,7%), kompetensi klinik (97,1%), serta perilaku profesional dan etika (97,1%). Dapat disimpulkan bahwa sebagian besar mahasiswa memiliki persepsi baik terhadap preceptor, dan preceptorship dinilai mendukung proses pembelajaran klinik secara optimal.